Dinamika Kinerja Lingkungan dan Implikasinya terhadap Pelaporan Keberlanjutan di Indonesia - Faisal Riza Rahman; Yulius Wahyu Setiadi (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
The objective of this study is to determine the impact of environmental performance on the sustainability reporting of companies in Indonesia, utilizing the PROPER scale as a measurement tool. This research examines whether there is an improvement in sustainability report disclosures associated with the environmental performance assessed through the PROPER scale. The study involves companies listed on the Indonesia Stock Exchange that have published annual and sustainability reports for five consecutive years. The analytical method employed is WarpPLS, with a total of 85 observations. WarpPLS is used to identify statistical relationships between environmental performance and the intensity of sustainability reporting. The findings indicate that there is an enhancement in sustainability report disclosures when the audit committee and board of directors hold regular meetings. Companies without governance committees tend to focus more on governance improvement rather than on disclosing sustainability reports. Good environmental performance, particularly in companies with specific industry types and the presence of governance committees, enhances sustainability reporting. However, companies with strong environmental performance tend to make the audit committee and board of directors focus on other responsibilities, given that the community already understands that these companies manage their environmental impact well. This study underscores the importance of the Indonesian government's support in encouraging, facilitating, and urging companies to achieve the gold category in the PROPER scale. This not only demonstrates good environmental performance but also enhances sustainability report disclosures. This research implies that good environmental performance should be accompanied by increased transparency in sustainability reporting to truly contribute to sustainable development.